Peranan Kepala Madrasah Dalam Meningkatkan Kinerja Guru Di Madrasah Aliyah Guppi Gunung Jati Kecamatan Gantarang Kabupaten Bulukumba - Samrawati Samrawati; Hasibuddin Hasibuddin; Surani Surani (Departement of Mathematics Education, 2023)
This research was conducted with the aim of: (1) knowing the role of the madrasah head in improving teacher performance at Guppi Gunung Jati Madrasah Aliyah; (2) knowing the supporting and inhibiting factors of the role of the madrasa head in improving teacher performance at the Guppi Gunung Jati Madrasah Aliyah.This study used a qualitative approach with a descriptive research type. Methods of data collection through observation, interviews and documentation in an effort to find out the role of the madrasa head in improving teacher performance at Guppi Gunung Jati Madrasah Aliyah.The results of this study indicate that the madrasa head has carried out his role in improving teacher performance as: (1) the madrasa head as a leader, motivator, educator and supervisor. (2) Factors supporting the madrasah head in improving teacher performance, namely (a) the quality of teachers who wish to develop their abilities, (b) the establishment of good communication, (c) the collaboration between educators and the head of the madrasa. The inhibiting factors for the role of the madrasa head in improving teacher performance are: (a) there is still a lack of civil servant education staff, (2) teachers are less able to divide their time between homework and school work, (c) innate abilities. The conclusion of this study is that the role of the head of the madrasah in improving teacher performance in Madrasah Aliyah Guppi Guning Jati has been carried out well through the program made by the madrasah.